Stage-based exergy analysis for a modern turboprop engine under various loading - Kirmizi, Mehmet; Aygun, Hakan; Turan, Onder (Pergamon-Elsevier Science Ltd, 2024)
Enhancements in propulsion systems have played a key role in promoting aircraft fuel efficiency, which serves to achieve global decarbonization goals. In particular, investigation by decoupling individual components of the whole engine explicitly provides insight about improvement potential. In this study, stage-based exergetic assessments of the turbomachinery components such as compressor and turbine for a large turboprop engine used in military cargo aircraft are performed for five different flight cases. As a novelty, a new index called specific irreversibility ratio (SIR) showing irreversibility per unit power is established. In this regard, exergy efficiency of compressor changes from 86.6 % to 96.3 % throughout the 14 stages whereas for whole compressor, it is measured as 89.3 %. On the other hand, exergy efficiency of gas turbine changes from 92.5 % to 91.8 % throughout 2 stages whereas, for power turbine, it varies from 89.1 % to 89.7 % throughout 2 stages. Moreover, SIR of air compressor diminishes from 12.94 % to 4.26 % throughout 14 stages whereas those of gas turbine and power turbine increase from 8.17 % to 8.84 % and from 11.52 % to 12.58 % along with two stages, respectively. As for effect of flight cases, exergy efficiency of whole compressor changes by 2 % whereas those of gas and power turbines vary by 0.2 % and 0.5 %, respectively throughout flight cases. However, improvement potential rate of air compressor experiences a change between 23.81 kW and 58.19 kW whereas it varies between 27.31 kW and 50.74 kW for gas turbine and between 26.24 kW and 36.23 kW for power turbine. It could be inferred that variation of exergetic metrics throughout stages is more apparent in comparison with those of flight cases. The methodology improved in this study could help in understanding stage-based efficiency of turbomachinery components at on-design and off-design conditions.
Keywords: Stage-based exergy; Turboprop; Aircraft; Compressor; Turbine